Chapter 5.37 The Profession of Research Management and Administration in Portugal - Cláudia Barbosa; Filipa Borrego; Teresa Costa; Ana Ferreira; Madalena Martins; Susana Moreira; José M. R. C. A. Santos; José Avelino Silva (Emerald Publishing Limited, 2023)
This chapter addresses the profession of research management and administration (RMA) in Portugal. It starts with a brief outline of the national research and innovation (R&I) ecosystem that contextualises the development of the profession. The RMA community is characterised and the expectations for the future of the RMA profession are summarised using data collected through a national online survey. It is posited that RMA in Portugal is an emergent career having developed key traits of a profession, namely common interests and practices, a concern with deepening specialised knowledge and skills, the existence of an organised network of practitioners, the offer of academic qualifications and training in the area, and the integration in international RMA communities of practice. Nevertheless, future developments in the European Research Area (ERA) are identified as a critical milestone that will influence the development and formal legislative institutionalisation of the RMA profession in Portugal.
10.1108/978-1-80382-701-820231071; 10.1108/978-1-80382-701-820231071; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262